On the Normalization of Diplomatic Relationship Between Israel and Muslim Countries: A Study of Classic Fiqh and Contemporary Fatwas - JM Muslimin; Mahmoud Mohamed Hosny (Al-Jami'ah Research Centre, 2021)
This article discusses the different legal opinions of Muslim scholars of various trends in the past and modern time, on the normalization of diplomatic relationship between Muslim countries and Israel. The article aims to compare among these different opinions and also to clearly define the common and specific argument on which they agreed, as well as to accurately define the points of disagreement. The focus of study will be the theoretical reasons as well as practical effects, through the analysis of fatwas and their context. The exploration will give the reader a clear understanding of the nature of these differences yet the conflicting arguments among them. This article follows the methodology of the jurisprudential and contextual analytical comparison. The research questions will follow this logical sequence: what are the general opinions of Muslim religious scholars regarding the issue of diplomatic normalization with Israel? what are the areas of agreements and differences between them? and what are the current fatwas and their reasons for their opinions in the perspective of Islamic law? However, in some points, due to its actual and comprehensive argument as well as the worldwide circulation, Yusuf al-Qaradhawi’s legal opinion and fatwa will be cited and referred longer than others as examining stone and completing legal validity and representing contemporary logics of prominent Muslim jurist. The article concludes some points of theoretical differences, similarities and practical implications as well as recommendations of notifications for future study. [Artikel ini membahas perbedaan pendapat antar sarjana muslim mengenai trend di masa lalu dan kini tentang normalisasi hubungan diplomatik antara negara muslim dan Israel. Artikel ini membandingkan perbedaan opini dan dan juga menjernihkan titik kesepahaman dan ketidaksepahaman yang disepakati bersama. Fokus pembahasan mulai dari aspek teoritis hingga efek praktis melalui analisis fatwa dan konteksnya. Pembahasan juga memberikan pemahaman bagi pembaca keadaan yang berbeda termasuk argumen konflik diantara mereka. Artikel ini menggunakan metode analisis perbandingan hukum dan kontekstual. Setidaknya ada dua pertanyaan yang akan dijawab yaitu apa pendangan umum sarjana muslim mengenai wacana normalisasi hubungan diplomatik dengan Israel dan apa fatwa terbaru serta penjelasannya dalam perspektif hukum Islam? Dalam beberapa hal, argumen aktual dan komprehensif mengikuti sirkulasi yang lebih luas. Fatwa dan pendapat Yusuf Qaradawi akan dikutip dan dirujuk lebih banyak sebagai pijakan serta validasi dan representasi komplit logika kontemporer bagi pemikir muslim ternama. Artikel ini menyimpulkan beberapa hal penting terkait perbedaan dan persamaan teoritis serta implikasi praktis, termasuk juga rekomendasi untuk kajian ini ke depan]